Contribution of Rehabilitation Nursing in Intensive Care Units - Virgínia Maria Pereira Prazeres; Catarina Dias Ribeiro; Goreti Filipa Santos Marques (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Currently, it is recognized that as important as surviving critical illness, is to live with quality, dignity and full exercise of citizenship, after discharge from intensive care. This recognition places an important focus on the role of the Specialist Nurse in Rehabilitation Nursing in Intensive Care Units. Objectives: To reflect on the contribution of Rehabilitation Nursing in Intensive Care Units. Main topics under analysis: complications resulting from hospitalization in intensive care; the Specialist Nurse in Rehabilitation Nursing in Intensive Care Units ; safety criteria for early rehabilitation; and barriers and facilitating factors in early rehabilitation in Intensive Care Units. Conclusion: the presence of Specialists Nurses in Rehabilitation Nursing in Intensive Care Units, in a consistent and sustained manner, is imperative. Their interventions, based on the best available evidence and attentive to the safety of the person in critical situation, can contribute to the improvement of the quality of care provided, which brings benefits both for the sick person/family and for hospital institutions.